2017
DOI: 10.17557/tjfc.303885
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Row Spacing and Plant Density on Yield and Yield Components of Peanut Grown as a Double Crop in Mediterranean Environment in Turkey

Abstract: This study was conducted at the Cukurova University research farm as a double crop in 2013 and 2014 in Adana, Turkey. The objective of this study was to determine the effect of row distance and plant density on yield and yield components of peanut(Arachis hypogaea L.) grown as a double crop. The experimental design was a split plot design with three replications. The Halisbey (Virginia type) variety was used as a plant material in this research. The row spacing was arranged 70 and 75 cm, and intra-row spacing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
30
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 18 publications
(36 reference statements)
15
30
3
9
Order By: Relevance
“…Also, it can be defined as the amount of harvest product per crop production area. Crop yield is expressed in kilograms (kg) or metric tons (t) of product per hectare (ha) [53]. Crop productivity per unit area is one of the essential indicators for agricultural development.…”
Section: Grain Yield Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it can be defined as the amount of harvest product per crop production area. Crop yield is expressed in kilograms (kg) or metric tons (t) of product per hectare (ha) [53]. Crop productivity per unit area is one of the essential indicators for agricultural development.…”
Section: Grain Yield Estimatesmentioning
confidence: 99%
“…Diverse methods can be applied for yield estimation at the farmer level. Estimating crop production through farmer interviews involves farmer recall from previous harvests (quantify the yield of the previous harvest) and farmer prediction (estimate the current yield based on the previous harvest) [53]. Most often, farmers predict their yield based on the previous harvest.…”
Section: Yield Estimation From Farmers' Fieldsmentioning
confidence: 99%
“…It is also in conformity with El Naim and Jabereldar [24] who observed that cowpea was influenced by sowing date intrarow spacing inoculation and nitrogen fertilization in the effect of plant density and cultivar on growth and yield of cowpea. Also the lack of varietal effect on the number of pods per plant contradicts earlier studies by Shambharkar, et al [25]; Onat, et al [14]; Dapaah, et al [26] and Sharma, et al [27] who reported varietal effect for number of pods per groundnut in a study to determine the responses of groundnut to plant spacing. Similar reports by Masenya [17] recorded significant varietal effect on number of pods per plant in evaluation of introduced cowpea lines.…”
Section: Nodules Per Plant Pods Per Plant and Seed Per Podmentioning
confidence: 83%
“…Groundnut monocropping in wide rows has been reported to lead to lower yields as a result of the sub-optimum plant population densities thus encouraging under-utilization of resources [13]. Studies of [14] indicated the positive effects of 50 cm row spacing against 60 cm row spacing on seed and pod yields of groundnut. [15] also showed reduction in weed density in 30 cm apart rows of peanut (Arachis hypogea) as compared to the weed density at wider spacing.…”
Section: Introductionmentioning
confidence: 99%
“…In this concern, Onat et al (2017) demonstrated that the oil content was decreased when the plant space was reduced. It is important to mention that seed oil content had the same response to increase in peanut plant density from 70 to 105 thousand plants per fed which indicating some degree of resource complimentarily under sandy soil conditions.…”
Section: Effect Of Peanut Plant Densitymentioning
confidence: 99%